TOWARDS A SUSTAINABLE CONFLICT OUTCOMES – CHALLENGES AND PERSPECTIVES (Annual of the Faculty of Philosophy in Skopje, 2024)
Predictions and expectations about more peaceful, safer and cooperative relationsin the international system by the beginning of the XXI century, unfortunately,did not come true. Namely, even today we are witnessing numerous violent internal aswell as conflicts between states, which solution is not even in sight. Hence, the dilemmaabout the applicability, efficiency and sustainability of the existing approaches in conflictmanaging and overcoming inevitably arises, i.e. do they offer an acceptable platformfor creating real solutions, as well, what are the main challenges and perspectives regardingsuch issue. Starting from this point of view, the paper analysis goal is to explorethe possible answers to the indicated dilemma. In this regard, the focus is specificallyplaced on the analysis of the existing challenges and perspectives from the theory-practicerelationship, as well as, from the so called exit solutions or outcomes related to theapplicability and sustainability of the instruments and methods of conflict settlementand resolution approaches.
Keywords: conflict; settlement; resolution; challenges; outcomes